Pedicle preservation in a Silurian rhynchonelliformean brachiopod from Herefordshire, England: soft-tissue or an artefact of interpretation? A Reply - Sutton, MD; Briggs, D; Siveter, D; Siveter, D (2008)
We consider the reinterpretation of Bethia by Bassett et al. (2008) to be flawed in several regards. Details of the pedicle rootlets and wrinkles strongly imply a soft-tissue structure rather than calcified sheath. The ornament is unusual, but equally so under either an orthide or a plectambonitoidean model. The reinterpretation of the 'deltial plates' as 'chilidial plates' is likely correct, but argues against a plectambonitoidean affinity by implying that the pedicle emerges between the valves. Other arguments presented in favour of a plectambonitoidean affinity are also discussed; we consider them unpersuasive. Finally, we contend that Bethia is sufficiently well characterised to deserve a taxonomic name. © 2008 Royal Society of Edinburgh.